2012
DOI: 10.4049/jimmunol.1102729
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Expression of Fas Ligand and Perforin Directs Effector CD8 T Cell Infiltration into Antigen-Challenged Skin

Abstract: Contact hypersensitivity (CHS) is a T cell response to hapten skin challenge of sensitized individuals proposed to be mediated by hapten-primed CD8 cytolytic T cells. Effector CD8 T cell recruitment into hapten challenge sites to elicit CHS requires prior CXCL1- and CXCL2-mediated neutrophil infiltration into the site. We investigated whether neutrophil activities directing hapten-primed CD8 T cell skin infiltration in response to 2, 4-dinitrofluorobenzene (DNFB) required FasL and perforin expression. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 47 publications
3
56
0
Order By: Relevance
“…3,7 We confirmed these findings by showing that neutrophil depletion greatly blocked the skin infiltration of CD8 + T cells following OXA challenge. Several T-cell chemokines including CXCL9 and CXCL10 have been shown to be important for the skin homing of T cells; 5,6,27 however, there was no change in gene expression of CXCL9 and CXCL10 in OXA-challenged ears following blockade of the LTB 4 -BLT1 axis or neutrophil depletion, suggesting that other important mediators could be more important for the skin homing of CD8 + T cells in OXA-induced contact dermatitis.…”
Section: Decreased Skin Inflammation In Blt1supporting
confidence: 65%
See 2 more Smart Citations
“…3,7 We confirmed these findings by showing that neutrophil depletion greatly blocked the skin infiltration of CD8 + T cells following OXA challenge. Several T-cell chemokines including CXCL9 and CXCL10 have been shown to be important for the skin homing of T cells; 5,6,27 however, there was no change in gene expression of CXCL9 and CXCL10 in OXA-challenged ears following blockade of the LTB 4 -BLT1 axis or neutrophil depletion, suggesting that other important mediators could be more important for the skin homing of CD8 + T cells in OXA-induced contact dermatitis.…”
Section: Decreased Skin Inflammation In Blt1supporting
confidence: 65%
“…3 Recent study further suggested that neutrophil expression of Fas ligand and perforin could promote CD8 + T-cell infiltration by inducing T-cell chemokine production in hapten-challenged skin. 7 These results together suggest a complex and dynamic cytokine network in the regulation of the skin recruitment of hapten-primed CD8 + T cells and neutrophils following hapten challenge during the elicitation phase.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 77%
See 1 more Smart Citation
“…Thus, the role of PMNs in promoting allograft injury has been extensively investigated in the past few years 31 . Besides their well-known effector functions, PMNs can also recruit activated CD8 + T cells through Fas ligand expression 32 . PMNs also facilitate antigen presenting cell (APC) activity, which is critical to T cell activation and differentiation, through the expression of MHC class II and co-stimulatory molecules 33 .…”
Section: Early Graft Inflammation and Alloimmunitymentioning
confidence: 99%
“…ACD is, at least in part, a cytotoxic T-cell-mediated immune response (Kehren et al, 1999;Kish et al, 2012). Granzyme B-and IFNg production (measured by ELISA or ELISpot) have been used as endpoints for cytotoxicity drug-allergic responses (Porebski et al, 2013) and could also be used for ACD.…”
Section: Allergen-driven Activation and Cytokine Secretionmentioning
confidence: 99%